2020
DOI: 10.1186/s12957-020-01879-8
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinoma of the pancreas with rare long-term survival: a case report

Abstract: Background Sarcomatoid carcinoma of the pancreas (SCP) tends to have similar or even worse prognosis than that of conventional pancreatic ductal adenocarcinoma. The clinical and pathological features of SCP remain poorly characterized owing to its rarity. Case presentation A 58-year-old man was admitted to our hospital with the chief complaints of upper abdominal pain and weight loss. Abdominal contrast computed tomography revealed a 5-cm low-density mass in the pancreatic body. Magnetic resonance cholangiopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Several terms have been used to describe this malignancy, including carcinosarcoma, pseudosarcoma, pseudocarcinoma, and spindle cell carcinoma[ 9 ]. The multiple names demonstrate the varied understanding of this disease, which these terms have been often used interchangeably, and their definitions vary among the reports[ 10 ]. According to the WHO classification (5 th edition, 2019) of pancreatic tumors assigns SCP under the category of undifferentiated carcinomas (UCP)[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several terms have been used to describe this malignancy, including carcinosarcoma, pseudosarcoma, pseudocarcinoma, and spindle cell carcinoma[ 9 ]. The multiple names demonstrate the varied understanding of this disease, which these terms have been often used interchangeably, and their definitions vary among the reports[ 10 ]. According to the WHO classification (5 th edition, 2019) of pancreatic tumors assigns SCP under the category of undifferentiated carcinomas (UCP)[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…UPC is categorized into two different types: undifferentiated carcinoma [with three variants: anaplastic undifferentiated carcinoma, sarcomatoid carcinoma (SCP), and carcinosarcoma] and undifferentiated carcinoma with osteoclast-like giant cells[ 5 , 12 ]. Hence, we present a case of SCP that is an extremely rare type of tumor, with only a few cases reported in the literature[ 5 , 9 , 10 , 13 - 21 , 31 - 36 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The survival benefit of surgery for SCP remains uncertain, and no therapeutic strategies for SCP have been established. We have already reported a rare case of SCP with long-term survival [ 3 ]. In that article, we concluded that the low proliferative activity of sarcomatous cells might have played a role in the prolonged survival of the patient.…”
mentioning
confidence: 99%